2018
DOI: 10.1210/jc.2017-02646
|View full text |Cite
|
Sign up to set email alerts
|

Glucagonoma With Necrolytic Migratory Erythema: Metabolic Profile and Detection of Biallelic Inactivation of DAXX Gene

Abstract: This is a report of glucagonoma with biallelic inactivation of DAXX determined by WES. The tumor manifested as glucagonoma syndrome with generalized NME. This case showed the relationship between hypoaminoacidemia and NME status. Further investigations are required to elucidate the underlying mechanisms of NME onset and glucagonoma tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
0
8
0
4
Order By: Relevance
“…There is a case report of FDG-avid pancreatic glucagonoma on FDG PET/CT in a patient with NME [ 25 ]. In the reported case, mild FDG uptake with SUVmax of 2.3 was seen in the tumor.…”
Section: Classification Of Pdmentioning
confidence: 99%
“…There is a case report of FDG-avid pancreatic glucagonoma on FDG PET/CT in a patient with NME [ 25 ]. In the reported case, mild FDG uptake with SUVmax of 2.3 was seen in the tumor.…”
Section: Classification Of Pdmentioning
confidence: 99%
“…Studies have shown that people with elevated circulating concentrations of glucagon over 7-fold higher than normal are at risk of protein wasting, hypoaminoacidaemia and weight loss [42]. Similarly, necrolytic migratory erythema, which is also seen in glucagonoma [43] and with prolonged treatment for congenital hyperinsulinaemia [44], may be linked with a decrease in circulating amino acids [45]. Therefore, because it is unknown whether a decrease in circulating amino acids will increase protein breakdown in lean tissue, the clinical consequences that could arise from the reduction of amino acids seen with NN1177 are currently unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time RT-PCR analysis RT-qPCR experiments were performed as previously described [10][11][12] . The FBP1 gene-speci c mRNA expression values were determined and normalized to those of β-actin as an internal control.…”
Section: Real-time Rt-pcr Analysismentioning
confidence: 99%